Transforming Growth Factor – β and Glioma - Handoko, Harrison; Hardiany, Novi Silvia (International Journal of Human and Health Sciences (IJHHS), 2020)
Transforming growth factor-beta (TGF-β) is a regulatory cytokine secreted by various types of cell such as stromal cell, immune cells and tumor cells. Signaling of TGF-β plays an important role in proliferation, differentiation and apoptosis regulation of various cell, including glial cell. Disruption in the signaling pathway of TGF-β is commonly seen in tumor cells and is believed to contribute to the initiation and progression of cancer cells. Changes in the chromosome accompanied by genetic mutation has been observed which causes TGF-β to act as an oncogene, a substance which promote normal cells to differentiate to cancer cells.Increased level expression of TGF-β molecules has been seen in more malignant gliomas which yields a lower prognosis for the patient compared to those with lower expression of TGF-β. Malignant gliomas are characterized by rapid proliferation, invasion of parenchyma and angiogenic capabilities, are most common type of primary brain tumors. Studies have now implemented specific targeted therapy which act as a treatment for glioma cases. This review will focus on the role of TGF-β in glioma and its application in the treatment of glioma. International Journal of Human and Health Sciences Vol. 04 No. 03 July’20 Page : 156-160